KEGIATAN ENGLISH CONVERSATION CLUB VIRTUAL UNTUK SISWA SMA KRISTEN KALAM KUDUS SUKOHARJO - Timotius, Anne Indrayanti; Kurniawan, Ardiyarso; Setyarini, Maria Christina Eko; Mali, Yustinus Calvin Gai (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service program aimed to serve 33 high school students in Kristen Kalam Kudus Sukoharjo Senior High School, a private school in Sukoharjo, Central Java, Indonesia. More specifically, the program was in the form of virtual English Conversation Club (ECC) activities for eight meetings. This ECC program was done primarily via Zoom Meeting and Google Classroom, facilitated by eight lectures and nine lecturer assistants. Each meeting lasted for 45 minutes. The facilitating lecturer started the ECC session by introducing learning activities, giving instructions, and opportunities for the participants to practice their English speaking with the lecturer's assistants in the breakout rooms. Afterward, ECC participants were asked to upload a short video based on the online practice to their social media accounts (like TikTok, Instagram, or YouTube). Details of activities and various technology tools in each ECC session were presented in this paper. Although there were some challenges, all the ECC activities went as the lecturers had planned. This paper ends with several suggestions for the improvement of similar ECC activities in the future.